1972
DOI: 10.1083/jcb.53.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor-Pigment Epithelial Cell Relationships in Rats With Inherited Retinal Degeneration

Abstract: Protein synthesis and displacement in photoreceptor and pigment epithelial cells of inbred normal (Fisher) and mutant (RCS) rats with inherited retinal degeneration has been studied by light and electron microscope radioautography . Groups of animals 14, 15,17,19,27, 35, and 50 days of age were injected with amino acids-H 3 and killed at subsequent time intervals . In normal rats, radioactive protein synthesized in the rod inner segments was incorporated into outer segment saccules and displaced outward ; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…When phagocytosis becomes dysregulated, as observed in the retinal dystrophic RCS rat, photoreceptors degenerate and blindness progressively ensues (Dowling and Sidman, 1962;Bok and Hall, 1971;LaVail, Sidman and O'Neil, 1972). Consequently the molecular mechanism of OS phagocytosis has been the subject of intense study for many years (reviewed in McLaughlin et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…When phagocytosis becomes dysregulated, as observed in the retinal dystrophic RCS rat, photoreceptors degenerate and blindness progressively ensues (Dowling and Sidman, 1962;Bok and Hall, 1971;LaVail, Sidman and O'Neil, 1972). Consequently the molecular mechanism of OS phagocytosis has been the subject of intense study for many years (reviewed in McLaughlin et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…It is well established that the integrity of the photoreceptor outer segment is indispensable for vision to take place and that disorganization of the outer segment is associated with degeneration of that same photoreceptor cell and loss of sight. Indeed, a disruption of photoreceptor outer segments is common to both human (Green et al, 1985;Farber et al, 1987;Rodrigues et al, 1987;Birnbach et al, 1994;Li et al, 1994Li et al, , 1995Milam et al, 1998;Green, 1999) and animal models (LaVail et al, 1972(LaVail et al, , 1975(LaVail et al, , 1982(LaVail et al, , 1985LaVail and Sidman, 1974;LaVail and Mullen, 1976a,b;Edwards and Szamier, 1977;Carter-Dawson et al, 1978;LaVail, 1979;Travis et al, 1989Travis et al, , 1991Narfström et al, 1991;Pittler and Baehr, 1991;Ma et al, 1995;Cheng et al, 1997;Kohl et al, 1998;Kennedy et al, 1999;Redmond et al, 1999) of various types of retinal degenerations. Although the organization of the outer segment is critical, other studies have demonstrated that visual acuity can be preserved despite some loss of photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning and atrophy of the RPE begin after the onset of degeneration, and subretinal accumulation of OS debris becomes apparent at P12 to P13. 4,[7][8][9] The retinal vasculature develops normally but begins to show signs of degeneration as early as 3 weeks of age. By 3 to 4 months of age, retinal vessels proliferate abnormally toward the RPE.…”
mentioning
confidence: 99%